Vegetation and climate change in the Pro-Namib and Namib Desert based on repeat photography: Insights into climate trends. (June 2019) - Rohde, Richard F.; Hoffman, M. Timm; Durbach, Ian; Venter, Zander; Jack, Sam
Abstract: This paper presents empirical evidence of historical vegetation and climate change in the arid Pro-Namib and hyper-arid Namib Desert spanning the late 19th century to the present based on one hundred archival landscape photographs that have been re-photographed or 'matched'. Each photo site was evaluated for changes in woody cover and taken together serve as a proxy for how climate has changed in the region. Vegetation change was related to values for precipitation and temperature derived from the Global Land Data Assimilation System for the period 1948–2017 as well as the number of fog days expected at a site. The resulting analysis reveals a trend of increased vegetation cover associated with increased precipitation (fog and rain) in the coastal Fogbelt and the inland Savanna transition with a shrinking of the hyper-arid Minimum zone between the two. These findings accord with projected effects of global warming on the Benguela upwelling system but are at variance with regional climate model forecasts that project widespread aridification. In the absence of long-term climate data, the results of this research are an important contribution of evidence-based knowledge of past climate trends and their relationship to future climate change scenarios for the region. Highlights: Global change models predict Namibia becoming hotter leading to aridification. We used historical photos of the Pro-Namib and Namib Desert to test this forecast. Correlations between historical climate values and vegetation change were analysed. Contrary to expectations, woody plant cover has increased at most locations. Past trends of increased rainfall and fog predict environmental futures.